2019
DOI: 10.1159/000499909
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Area Analysis of the Head of the Caudate Nucleus in Huntington’s Disease

Abstract: Background: Caudate nucleus atrophy is a well-known neuroimaging feature of Huntington’s disease (HD). Some researchers have reported a decrease in the volume of the striatum on magnetic resonance images (MRIs) even in the presymptomatic stage of the disease. Despite the many neuroimaging studies on HD, the optimal method for measuring the caudate nucleus area on MRIs and the most effective cutoff values for diagnosing HD remain unclear. Objectives and Methods: To define suitable imaging sequences and cutoff v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…However, physiological volume of the caudate nucleus in both MR tomography and VBM, as seen in this patient, is a very uncommon finding in HD and stands in contrast to the most recent report of Furukawa et al, who reported a fundamental reduction in the head of the caudate nucleus in patients with HD compared to sex-and age-matched healthy individuals [6]. Possible reasons for those discrepancies include the small sample size and the considerable range of symptom duration prior to scanning in Furukawa's study, the atypical clinical symptoms of our patient, low amount of CAG repeats and relatively short duration of illness, resulting in preserved caudate nucleus volume.…”
Section: Discussioncontrasting
confidence: 92%
“…However, physiological volume of the caudate nucleus in both MR tomography and VBM, as seen in this patient, is a very uncommon finding in HD and stands in contrast to the most recent report of Furukawa et al, who reported a fundamental reduction in the head of the caudate nucleus in patients with HD compared to sex-and age-matched healthy individuals [6]. Possible reasons for those discrepancies include the small sample size and the considerable range of symptom duration prior to scanning in Furukawa's study, the atypical clinical symptoms of our patient, low amount of CAG repeats and relatively short duration of illness, resulting in preserved caudate nucleus volume.…”
Section: Discussioncontrasting
confidence: 92%
“…1 The prominence of caudate head atrophy indicated several extrapyramidal diseases, including Huntington disease, Huntington disease-like 2 (HDL-2), chorea-acanthocytosis (ChAc), and McLeod syndrome. [1][2][3] Although his low-density lipoprotein and apolipoprotein B levels decreased, his vitamin E levels were normal; thus, hypobetalipoproteinemia was unlikely. Acanthocytes are not present in Huntington disease, therefore it was excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the consideration of neuroacanthocytosis and inherited disorders of lipoprotein metabolism (eg, abetalipoproteinemia and hypobetalipoproteinemia); the latter leads to vitamin E malabsorption . The prominence of caudate head atrophy indicated several extrapyramidal diseases, including Huntington disease, Huntington disease–like 2 (HDL-2), chorea-acanthocytosis (ChAc), and McLeod syndrome . Although his low-density lipoprotein and apolipoprotein B levels decreased, his vitamin E levels were normal; thus, hypobetalipoproteinemia was unlikely.…”
Section: Discussionmentioning
confidence: 99%